Penyuluhan Masyarakat Sehat, Kulit Sehat: Program Pengabdian Masyarakat - Firmansyah, Roby Syah Putra (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Skin health problems are still an important issue in various communities, especially in areas with limited sanitation and access to health services. This community service activity aims to increase public knowledge about how to care for healthy skin and prevent skin diseases. The method used is counseling and direct demonstration to residents in Sukamaju Village, with an educational and participatory approach. The results of the activity showed an increase in participants' knowledge about cleanliness and skin care. This activity is expected to increase public awareness of the importance of maintaining skin health as part of a healthy lifestyle.